2018
DOI: 10.1111/1365-2745.13045
|View full text |Cite
|
Sign up to set email alerts
|

Evolution during population spread affects plant performance in stressful environments

Abstract: Reliable predictions of population spread rates are essential to forecast biological invasions. Recent studies have shown that populations spreading through favourable habitat can rapidly evolve higher dispersal and reproductive rates at the expansion front, which accelerates spread velocity. However, spreading populations are likely to eventually encounter stressful conditions in the expanded range. How evolution during spread in favourable environments affects subsequent population growth in harsher environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 55 publications
(92 reference statements)
0
11
0
7
Order By: Relevance
“…However, these evolutionary changes may affect how populations subsequently respond to stressful environments such as those expected during range shifts under climate change. In experimental invasions of A. thaliana , an evolutionary increase in seed size over six generations of spread was associated with a subsequent reduction in population performance under drought stress (Lustenhouwer et al 2019). Thus, intraspecific variation in dispersal and seed traits and their evolution will influence the ability of plants to respond to anthropogenic and global climate change.…”
Section: Relevance Under Anthropogenic and Global Climate Changementioning
confidence: 99%
“…However, these evolutionary changes may affect how populations subsequently respond to stressful environments such as those expected during range shifts under climate change. In experimental invasions of A. thaliana , an evolutionary increase in seed size over six generations of spread was associated with a subsequent reduction in population performance under drought stress (Lustenhouwer et al 2019). Thus, intraspecific variation in dispersal and seed traits and their evolution will influence the ability of plants to respond to anthropogenic and global climate change.…”
Section: Relevance Under Anthropogenic and Global Climate Changementioning
confidence: 99%
“…Several recent studies have shown that alien plants can undergo rapid evolution through trait adaptation to novel selection pressures (e.g. Molina-Montenegro et al 2018;van Boheemen et al 2019a;Lustenhouwer et al 2019;Brandenburger et al 2019a, b). Rapid trait adaptation may be driven by several processes; for example, the Evolution of Increased Competitive Ability (EICA) hypothesis posits that there is an evolutionary shift from costly defensive abilities to competitive performance in introduced populations, due to the absence of co-introduced specialist enemies (Blossey and Notzold 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Other traits relating to plant phenology (Turner et al 2014) and resource acquisition efficiency (e.g. specific leaf area, leaf and stem dry matter content, carbon to nitrogen ratio of seeds and leaves, Wright et al 2004;Grassein et al 2010)) have also been shown to rapidly change following introduction as a result of competition for novel resources (Gioria and Osborne 2014;Lustenhouwer et al 2019). Many recent studies have shown that climate niche envelopes occupied by invasive plants in their introduced ranges can differ substantially to native ranges and exposure to novel climatic regimes may select for divergent traits of alien plant populations (Early and Sax 2014;Moran and Alexander 2014;van Boheemen et al 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…This means relationships between stress resistance and dispersal can be equally driven by fitness expectations after immigration in novel environments (Renault et al, 2018). In some cases, traits or contexts favoring dispersal do actually favor stress tolerance (Lustenhouwer et al, 2019). As the probability of arriving in, or crossing, marginal/suboptimal habitat should increase in heterogeneous environments, stress-resistant individuals may eventually profit most from dispersal, giving rise to positive correlations between these traits in such contexts.…”
Section: Introductionmentioning
confidence: 99%